Drivers of dietary behaviours in women living in urban Africa: a systematic mapping review - (:unkn) unknown (My University, 2017)
Abstract Objective To (i) systematically review the literature to determine the factors influencing diet and dietary behaviour in women living in urban Africa; (ii) present these in a visual map; and (iii) utilize this to identify potentially important areas for future research. Design Systematic mapping review. The review protocol was registered at PROSPERO ( http://www.crd.york.ac.uk/PROSPERO/ ; registration number CRD42015017749). Six databases were systematically searched, followed by reference and citation searching. Eligibility criteria included women aged 18–70 years living in urban Africa, any design/methodology, exploring any driver, using any measure of dietary behaviour. Quality appraisal occurred parallel with data extraction. Twelve predominantly cross-sectional quantitative studies were included; reported in seventeen publications. Determinants were synthesized narratively and compiled into a map adapted from an existing ecological model based on research in high-income countries. Setting Urban Africa. Subjects African women aged 18–70 years. Results Determinants significantly associated with unhealthy dietary behaviour ranged from the individual to macro level, comprising negative body image perception, perceptions of insufficient food quantity and poorer quality, poorer food knowledge, skipping meals, snacking less, higher alcohol consumption, unhealthy overall lifestyle, older age, higher socio-economic status, having an education, lower household food expenditure, frequent eating outside the home and media influence. Marital status and strong cultural and religious beliefs were also identified as possible determinants. Conclusions Few studies have investigated drivers of dietary behaviours in urban African settings. Predominantly individual-level factors were reported. Gaps in the literature identified a need for research into the neglected areas: social, physical and macro-level drivers of food choice.
Keywords: African Research